The Effect Of Customer Experience On Repurchase Intention With Customer Engagement As An Intervening Variable - Lia Novita Sari; Sri Padmantyo (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
In this era, the business world is increasingly competitive, making companies look for creative ideas and breakthroughs so that consumers remain loyal and have a repurchase intention on the products offered. Several variables, including customer experience and customer engagement, are influential factors in the occurrence of repurchase intention. This research aims to analyze the impact of customer experience to repurchase intention, with customer engagement as an intervening variable. This type of research is explanatory and intends to describe and test the causality between the variables studied. The data sample used 223 skincare user respondents with a nonprobability sampling method. For research testing, two sub-models were carried out, namely the outer and inner models, then data was analyzed using the Structural Equation Model Partial Least Square (SEM-PLS) method. This study’s results indicate a significant effect of customer experience on repurchase intention, with customer engagement as an intervening variable. Based on these results, to achieve optimal outcomes, the company needs to ensure that customers are actively involved in interactions with the company, whether through customer service, social media, or other communication channels. By increasing customer engagement, companies can strengthen the effect of customer experience to repurchase intention, thereby improving business performance and increasing customer loyalty